Employees' right to strike in sri lanka - a statutory decoration? - Mudalige, N.K.K. (University of Jaffna, 2016)
The statutory Right to Strike plays an important role in the consideration of trade union actions where the said right is utilized to demand solutions to employees' tribulations. As per S.R. De Silva (1973) “The right to Strike is one of the most fundamental rights enjoyed by employees and their unions, and is an integral part of their right to defend their collective economic and social interests”. Although some indications are evident in Sri Lankan labour related enactments, “Right to Strike” has still not clearly recognized in any one of them. Yet it is sought under the study whether the statutory right to strike is available to Sri Lankan employees and whether such implied recognition is sufficient. Methodology followed in the study is exploratory where documented sources are analyzed to find-out the legal standing of right to strike. Related Legislations and judicial decisions were used as primary sources and as secondary sources commentaries, journal articles and conference proceedings would be utilized in this study. For the purpose of comparison of legal regimes it was selected United Kingdom and South African Law on Strikes. Recommendations would express required legal framework to Sri Lanka to avoid the right to strike being a worthless statutory decoration based on the comparative study.
Keywords: Collective action; Employees' rights; Strikes; Trade unions